Comparative Study of Subseafloor Microbial Community Structures in Deeply Buried Coral Fossils and Sediment Matrices from the Challenger Mound in the Porcupine Seabight - Hoshino, Tatsuhiko; Morono, Yuki; Terada, Takeshi; Imachi, Hiroyuki; Ferdelman, Timothy G.; Inagaki, Fumio (Frontiers in Microbiology, 2011)
Subseafloor sedimentary environments harbor remarkably diverse microbial communities. However, it remains unknown if the deeply buried fossils in these sediments play ecological roles in deep microbial habitats, or whether the microbial communities inhabiting such fossils differ from those in the surrounding sediment matrix. Here we compare the community structures of subseafloor microbes in coldwater coral carbonates (Madrepora oculata and Lophelia pertusa) and the clay matrix. Samples were obtained from the Challenger Mound in the Porcupine Seabight at Site U1317 Hole A during the Integrated Ocean Drilling Program Expedition 307. DNA was extracted from coral fossils and the surrounding sedimentary matrix at 4, 20 and 105 meters below the seafloor. 16S rRNA genes of Bacteria and Archaea were amplified by PCR, and a total of 213,792 16S rRNA gene-tagged sequences were analyzed. At the phylum level, dominant microbial components in both habitats consisted of Proteobacteria, Firmicutes, Nitrospirae, Chloroflexi and Miscellaneous Crenarchaeota Group (MCG) at all three of the depths examined. However, at the genus and/or species level (similarity threshold 97.0%), the community compositions were found to be very different, with 69-75% and 46-57% of bacterial and archaeal phylotypes not overlapping in coral fossils and the clay matrix, respectively. Species richness analysis revealed that bacterial communities were generally more diverse than archaea, and that the diversity scores of coral fossils were lower than those in sediment matrix. However, the evenness of microbial communities was not significantly different in all the samples examined. No eukaryotic DNA sequences, such as 18S rRNA genes, were obtained from the corals. The findings suggested that, even at the same or similar depths, the sedimentological characteristics of a habitat are important factors affecting microbial diversity and community structure in deep subseafloor sedimentary habitats.